Hubungan antara Usia Menarche dengan Tinggi Badan - Zarah Alifani Dzulhijjah; Ida Royani; Sri Julyani (Indonesian Journal of Health, 2022)
The age of menarche has shifted to a younger age. Allegedly this is caused by better nutrition and health in the current generation. This study aims to determine the relationship between menarche age and height in female students class 2011-2013 at the Faculty of Medicine, Muslim University of Indonesia. The method used is observational analytic with cross-sectional research design. The data taken is primary data by measuring the height of the researcher and asking the sample directly about the age of menarche. The data is then processed by statistical tests. The method used is the chi-square method. Value on Sig. (2-tailed) shows a value of 0.006 which is <0.05. This means that there is a significant relationship between the age of menarche and the height of female students in the 2011-2013 batch at the Faculty of Medicine, Muslim University of Indonesia. The conclusion of this study is that there is a significant relationship between the age of menarche and the height of 2011-2013 female students at the Faculty of Medicine, Muslim University of Indonesia.